Inhibition of Heat Shock Protein 90β by Catalpol: A Potential Therapeutic Approach for Alleviating Inflammation‐Induced Cartilage Injuries in Osteoarthritis - Zhenwei Zhou; Binghua Zhang; Lang Liu; Jie Yang; Yuting Wang; Cheng Lv; He Zhang; Yuchi Wei; Zhanliang Jiang; Zeyu Peng; Daqing Zhao; Xiangyang Leng; et al. (Advanced Science)
Abstract Osteoarthritis (OA) is a degenerative joint disease characterized by the metabolic dysfunction of chondrocytes. A promising therapeutic strategy for OA involves suppressing the catabolism of the chondrocyte and promoting its anabolism to restore joint homeostasis. Here, it is demonstrated that Catalpol, a natural compound, can promote chondrocyte anabolic and proliferation, while inhibiting the catabolic activities and oxidative stress, thereby maintaining the dynamic balance of the extracellular matrix and alleviating inflammation‐induced cartilage damage. Mechanistically, it has been discovered that Catalpol acts as a direct inhibitor of heat shock protein 90β (Hsp90β), and the amino acids ASP88, THR179, ASP49, and ASN46 of N‐terminal domain‐Hsp90β are confirmed as the binding sites for Catalpol. Knockdown of Hsp90β in primary chondrocytes demonstrates a similar biological effect as Catalpol treatment. Moreover, to develop a nanoparticle‐based interventional platform for OA management, biodegradable mesoporous silica nanoparticles (bMSN) are prepared to load Catalpol (Ca‐bMSN). The engineered Ca‐bMSN is able to penetrate into the chondrocytes, prolong retention in the joint space, and mitigate OA progression. These findings shed light on a potential mechanism by which Catalpol modulates chondrocyte metabolism, offering a promising therapeutic strategy for OA treatment.